If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(4p+2)+8=35
We simplify the equation to the form, which is simple to understand
9(4p+2)+8=35
Reorder the terms in parentheses
+(+36p+18)+8=35
Remove unnecessary parentheses
+36p+18+8=+35
We move all terms containing p to the left and all other terms to the right.
+36p=+35-18-8
We simplify left and right side of the equation.
+36p=+9
We divide both sides of the equation by 36 to get p.
p=0.25
| 25b+20b+4=26+6 | | 2ln(x)=14 | | y=15-9x | | y=ln(4x-4) | | .89x+10=.99 | | 10*10*10*10*10*10= | | -2(2n/5)=4 | | -2w-4(-5x+3w)-4x= | | (x+10)(x+10)=x^2+cx+d | | 25a+30a=25a+100 | | x^2+4xy+4y^2-6x+5=0 | | 2a+3a+8a=144 | | 11x+5+2x=(3+10)x-6+11 | | 12x+10+3x=(2+13)x-6+16 | | 7a^2+49a-210=0 | | B*2-a*3+1=0 | | 11x+1y=3 | | 3m+9=5m-5 | | x+2*64=6*64 | | 10(x+1)=5x+25 | | 2(w+l)=2w+2l | | 3(x+20)=15 | | x/6-x/7=3/7 | | (a-16)/5=29 | | a-16/5=29 | | a-16/5=-8 | | 12x-18=10x | | 7(v-4)=14 | | (a-16)/5=-8 | | -6u+3=-3(u-3) | | 6sen(A)-3=0 | | -3m=-4+8 |